Study on the Application of Surface Modeling Algorithm - Xumin Liu; Weixiang Xu; Jing Xu; Yong Guan (2010 International Conference on Measuring Technology and Mechatronics Automation, 2010)
Surface modeling algorithms were designed using models including TC-Be¿zier, B spline curve with shape parameter, trigonometric B spline curve with shape parameter and hyperbolic polynomial B spline curve. The SMS (Surface Modeling System) was developed, OpenGL as the graph library, in Microsoft Visual C++ 6.0 programming environment. Founded the uniform platform of surface modeling, and realized and verified the proposed algorithms. The experiment result showed that the algorithms were feasible and the SMS was practicable.